HARVESTING PIEZOELECTRIC ENERGY ON A HIGHWAY IN CALLAO TO CHARGE LOW CALLAO TO CHARGE LOW-CONSUMPTION EQUIPMENTFIRST - RUBIÑOS-JIMENEZ, SANTIAGO (2024)
CURRENTLY IN CALLAO THERE ARE AREAS WITH HIGH VEHICLE DENSITY, WHICH REDUCES THE USEFUL LIFE OF THE ROAD. HOWEVER, IT IS POSSIBLE TO TAKE ADVANTAGE OF THE MECHANICAL ENERGY GENERATED BY THESE VEHICLES WHEN THEY ARE TRAVELING ON THE ROADS TO PRODUCE ELECTRICAL ENERGY. THE OBJECTIVE OF THIS STUDY IS TO OBTAIN ELECTRICAL ENERGY PRODUCED BY VEHICLES TRAVELING THROUGH THE DISTRICT OF CALLAO TO CHARGE LOW-CONSUMPTION EQUIPMENT. IN THIS SIMULATION STUDY, LIGHT AND HEAVY LOAD VEHICLES TRANSITING THROUGH CALLAO, IN AREAS WITH HIGH VEHICULAR TRAFFIC, WERE CONSIDERED IN ORDER TO ANALYZE IF THE ENERGY DEMAND CAN BE COVERED TO CHARGE LOW POWER CONSUMPTION EQUIPMENT. IT WAS OBTAINED IN THE TESTS THAT THE MINIMUM ENERGY PRODUCED IS 5.02 KWH TAKING INTO ACCOUNT THAT THE AVERAGE TRAFFIC IS 100 VEHICLES TRAVELING AT A SPEED OF 40 KM/H AND THE HIGHEST ENERGY PRODUCTION IS 26.18 KWH WITH AN AVERAGE TRAFFIC OF 400 VEHICLES AT A SPEED OF 80 KM/H AND THAT, WHEN THE ACCUMULATION OF ENERGY OBTAINED ON THE ROAD DAILY WAS MEASURED, VALUES BETWEEN 13.97 KW/H AND 33.18 KW/H WERE OBTAINED AT THE MOMENT WITH THE LOWEST VEHICLE FLOW AND THE HIGHEST VEHICLE FLOW, RESPECTIVELY. © 2024 LATIN AMERICAN AND CARIBBEAN CONSORTIUM OF ENGINEERING INSTITUTIONS. ALL RIGHTS RESERVED.